Sufism moral education as an effort to strengthen student’s character in the era of digital disruption - M. Mas'ud; F. Fauzan (Research and Development in Education (RaDEn), 2025)
Sufism moral education plays an important role in shaping the character of students, especially in Islamic universities. The era of digital disruption presents a major challenge for the formation of student character, where the widespread use of information and communication technology can affect moral and ethical values. This study aims to analyze the role of Sufism moral education in strengthening the character of students at the State Islamic University of Kiai Haji Achmad Siddiq Jember (UIN KHAS Jember) amidst rapid digital developments. This study uses a qualitative approach with a case study method, which involves in-depth interviews and observations of students and lecturers at UIN KHAS Jember. The results of the study indicate that Sufism moral education can increase spiritual awareness, self-control, and ethical attitudes of students in interacting in cyberspace. However, its application still needs strengthening, especially in aligning Sufism values with the challenges of the digital era. Therefore, this study also compiles a model of Sufism moral education that is more relevant to the needs of the times, which can be applied in the curriculum at UIN KHAS Jember. This research provides theoretical contributions to Islamic education literature and practical contributions to the development of Sufism-based education curriculum to strengthen students' character.